Immune microenvironment of cholangiocarcinoma: Biological concepts and treatment strategies - Yu, Xianzhe; Zhu, Lingling; Wang, Ting; Chen, Jiang (Frontiers in Immunology, 2023)
Cholangiocarcinoma (CCA) is characterized by a poor prognosis and a tragically limited armamentarium of drugs and treatments. Chemotherapy using gemcitabine with cisplatin (Gem+Cis) is the only validated first-line therapy for advanced CCA patients. However, this standard treatment offers just palliation and results in a median survival of less than 1 year. Recent years have seen the resurgence of immunotherapy study and its ability to inhibit cancer growth by impacting the tumor microenvironment (TME). However, immunotherapy, like immune checkpoint blockade (ICB), appear less effective in CCA than other cancers. Although a number of factors, such as exuberant desmoplastic reaction, are responsible for CCA treatment resistance, the existing literature on CCA reveals that an inflammatory and immunosuppressive environment is the most common factor. However, mechanisms activating the immunosuppressive TME contributing to CCA drug resistance is complicated. Therefore, gaining insight into the interplay between immune cells and CCA cells as well as natural development and evolution of immune TME would provide targets for therapeutic intervention and improve therapeutic effect by developing multimodal and multiagent immunotherapeutic approaches of CCA to overcome immunosuppressive TME. In this review, we aim to address the role of an inflammatory microenvironment-CCA crosstalk and reinforce the importance of inflammatory cells in the TME, eventually highlighting the explanatory and therapeutic shortcomings of immunotherapy monotherapy and proposing promising combinational immunotherapeutic strategies.